Avaliação da resistência de união entre cimento e uma vitro cerâmica condicionada com diferentes tempos de ácido fluorídrico 5% e 10% - estudo in vitro - Veronese, Carolina Bauer Godoy (2017)
Objective: to assess the effect of different hydrofluoric acid (HF) etching times at concentrations of 5% and 10% on the bond strength of RelyX Ultimate resin cement to a zirconia-reinforced lithium silicate ceramic of commercial brand Vita Suprinity (VS), for which the manufacturer recommends using 5% HF for 20". Method: experimental and completely randomized study with 8 treatments (n=8). Each ceramic sample was etched with hydrofluoric acid (HF) at different times and concentrations: 5% for 20, 30, 40, and 60 s, and 10% for 10, 20, 30, and 40 s; subjected to roughness (Ra) analysis, followed by the cementation protocol applying hydrofluoric acid, RelyX Ceramic Primer silane, Single Bond Universal adhesive, and RelyX Ultimate resin cement. Bond strength was assessed by the microshear test followed by fracture pattern analysis. Results: the 5%/20" treatment showed the statistically lowest bond strength of 21.96 MPa (p<0.01), differing from 10% HF treatment at the four times studied: 10" = 29.59 MPa, 20" = 29.77 MPa, 30" = 29.68 MPa, and 40" = 30.78 MPa (p<0.01). The 10%/40" treatment showed the highest bond strength (30.78 MPa), differing only from 5%/20" (21.96 MPa). The fracture pattern was predominantly adhesive. Conclusion: hydrofluoric acid etching increases surface roughness of the Vita Suprinity ceramic at both concentrations and their different times of exposure, showing significant differences in adhesive bond strength only when concentration and etching time vary widely, and with mostly adhesive rupture occurring in the adhesive interface. The concentration of 5% hydrofluoric acid for 30" or 10% for 10" or 20" showed higher bond strength than the manufacturer's protocol, but there were no wide and shallow porosities in SEM. This suggests the increase in exposure time recommended by the manufacturer from 20" to 30" or the use of higher concentrations of acid, such as 10% at 10" or 20", for more effective results.